Seven Grade Students' Vocabulary Mastery Through the Use of a Vocabularies List in Online Learning - Hilma Pitriana (Universitas Cokroaminoto Palopo, 2021)
The goal of this study is to see how the vocabularies list technique can help students in class VII C at MTs Khazanah Kebajikan improve their vocabulary mastery. The goal of this study was to use the "Vocabularies List" technique to help students in class VII C improve their vocabulary mastery. Mixed Method research is used in this type of study, with quantitative data coming in the form of a percentage of students' vocabulary test scores, and qualitative data coming in the form of observation and direct and online interviews. The students' vocabulary mastery improved as a result of the vocabularies list technique, according to the findings. Students can understand and identify the meanings of English words. Students can gradually add new vocabulary, which will help them improve their English skills. The vocabulary arrangement is tailored to the student's material and designed to be as appealing as possible so that students are interested in learning it.